Examining the contribution of Islamic bank to Indonesia economic growth - Taqiyya, Faz Fachry; Sudarsono, Heri; Perdana, Andika Ridha Ayu (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
This study thoroughly examines the impact of Islamic finance on economic growth in Indonesia, considering key variables such as total financing, total deposits, inflation, and trade openness. This study uses quarterly data covering the period from the first quarter of 2005 to the fourth quarter of 2021, providing a comprehensive overview of the dynamics between Islamic finance and economic growth for more than a decade. Through panel data regression analysis using the ARDL model, this study effectively explains the interaction between the dependent and independent variables and identifies the long-term impact of Islamic finance variables on Indonesia's economy. The findings indicate that Islamic finance positively contributes to long-term economic growth in Indonesia, with increases in total financing and deposits playing crucial roles in accelerating economic growth. These results underscore the importance of further developing the Islamic finance sector as a key driver of economic growth with significant implications for policies that support financial inclusion and macroeconomic stability. This study offers new insights for policymakers and financial practitioners to maximize the potential of Islamic finance to promote sustainable economic growth in Indonesia.